Air Effect on the Ideality of p‐Type Organic Field‐Effect Transistors: A Double‐Edged Sword. (9th October 2019) - Wu, Xiaofeng; Jia, Ruofei; Jie, Jiansheng; Zhang, Mi; Pan, Jing; Zhang, Xiujuan; Zhang, Xiaohong
Abstract: Organic field‐effect transistors (OFETs) often deviate from ideal behaviors in air, which masks their intrinsic properties and thus significantly impedes their practical applications. A key issue of how the presence of air affects the ideality of OFETs has not yet been fully understood. It is revealed that air atmosphere may exert a double‐edged sword effect on the active semiconductor layer when determining the ideality of OFETs fabricated from p‐type crystalline organic semiconductors. Upon exposing the as‐fabricated device to air, water and oxygen mainly function as efficient p‐type dopants for the active layer in the contact regions, enhancing charge carrier injection and consequently improving device ideality. Nevertheless, as the exposure time increases, the trapping centers for the injected minority charge carriers appear in the channel region, leading to degradation of device ideality. Inspired by the double‐edged sword behavior of air, a near‐ideal OFET is achieved by ingeniously utilizing the doping/positive effect and eliminating the trapping/negative effect. The effect of air on the ideality of p‐type OFETs is clarified, which not only illuminates some common observations of OFETs in air but also offers useful guidance for the construction of high‐performance ideal OFETs. Abstract : The mechanism underlying the ideality evolution of p‐type organic field‐effect transistors in air is revealed. Water and oxygen in air can act as a double‐edged sword in determining the device ideality. In light of this mechanism, a near‐ideal behavior is achieved by selectively doping the contact areas and controlling the measurement environment.